2022
DOI: 10.1038/s41416-022-01972-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatic hits in mismatch repair genes in colorectal cancer among non-seminoma testicular cancer survivors

Abstract: BACKGROUND: Non-seminoma testicular cancer survivors (TCS) have an increased risk of developing colorectal cancer (CRC) when they have been treated with platinum-based chemotherapy. Previously we demonstrated that among Hodgkin lymphoma survivors (HLS) there is enrichment of rare mismatch repair (MMR) deficient (MMRd) CRCs with somatic hits in MMR genes. We speculate that this phenomenon could also occur among other cancer survivors. We therefore aim to determine the MMR status and its underlying mechanism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We hypothesize that the development of CRC in TCS may differ from that observed in the general population due to (epi)genetic changes caused by specific anticancer treatments 8 . Increasing evidence suggests that sporadic CRCs result from the stepwise accumulation of multiple somatic mutations, which is also observed in CRCs in TCS 25 . Kuijk et al showed that both capecitabine–oxaliplatin chemotherapy and radiotherapy are mutagenic in colorectal stem cells and that the mutational burden was significantly increased in normal noncancerous cells, in addition to the typical accumulation of mutations associated with aging, applying whole genome sequencing 26 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We hypothesize that the development of CRC in TCS may differ from that observed in the general population due to (epi)genetic changes caused by specific anticancer treatments 8 . Increasing evidence suggests that sporadic CRCs result from the stepwise accumulation of multiple somatic mutations, which is also observed in CRCs in TCS 25 . Kuijk et al showed that both capecitabine–oxaliplatin chemotherapy and radiotherapy are mutagenic in colorectal stem cells and that the mutational burden was significantly increased in normal noncancerous cells, in addition to the typical accumulation of mutations associated with aging, applying whole genome sequencing 26 .…”
Section: Discussionmentioning
confidence: 94%
“…8 Increasing evidence suggests that sporadic CRCs result from the stepwise accumulation of multiple somatic mutations, which is also observed in CRCs in TCS. 25 Kuijk et al showed that both capecitabine-oxaliplatin chemotherapy and radiotherapy are mutagenic in colorectal stem cells and that the mutational burden was significantly increased in normal noncancerous cells, in addition to the typical accumulation of mutations associated with aging, applying whole genome sequencing. 26 They found the pattern of single base substitutions (SBS) to be consistent with an SBS mutational signature from the Catalogue of Somatic Mutations in Cancer that has been ascribed to prior platinum-based treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage I nonseminomas had a good prognosis, with 99.1% of disease‐specific 15‐year survivors. It is treatable with active surveillance 129 . Post‐orchiectomy treatment for stage II and III non‐seminomas includes cisplatin‐dependent chemotherapy and RPLND, depending on lymph node linkage and whether tumor biomarkers stay high after orchiectomy.…”
Section: Introductionmentioning
confidence: 99%
“…It is treatable with active surveillance. 129 Post‐orchiectomy treatment for stage II and III non‐seminomas includes cisplatin‐dependent chemotherapy and RPLND, depending on lymph node linkage and whether tumor biomarkers stay high after orchiectomy. For stage II nonseminoma, chemotherapy with or without RPLND had a 5‐year relapse‐free rate ranging from 96% to 97%.…”
Section: Introductionmentioning
confidence: 99%